Peningkatan Daya Saing dalam Pengembangan Karir Generasi-Z di Jurusan Manajemen Universitas Tadulako - Rynaldi Sn Kasim; Lina Mahardiana; Risnawati Risnawati; Faruq Lamusa (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze and examine the effect of improving competitiveness on the career development of Generation Z students in the Management Department at Universitas Tadulako. Methodology: This research applied a quantitative approach using a simple random sampling method with 70 respondents from a population of 229 students in the 2021 cohort. Primary data were collected using questionnaires and analyzed using simple linear regression with SPSS 25.0. Results: The findings demonstrate that competitiveness, measured through both soft and hard skills, has a positive and significant influence on career development. Students who actively improve their technical expertise, adaptability, and interpersonal abilities are more likely to advance their careers. Conclusions: Enhancing competitiveness significantly contributes to the career development of Generation Z students. Educational institutions play a crucial role in providing relevant curricula, training, and practical experiences that strengthen both technical and interpersonal competencies to meet labor market demands. Limitations: The study is limited by its relatively small sample size (70 respondents) and the use of a single predictor variable. This constrains the generalization of the findings and excludes other relevant factors, such as curriculum quality, internships, mentoring, and labor market conditions. Contribution: This study enriches the literature on career development by emphasizing the importance of integrating soft and hard skills to enhance competitiveness among Generation Z. It provides practical insights for universities and policymakers to design strategies that align education with labor market requirements.